2023
DOI: 10.1001/jamanetworkopen.2023.39108
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Lead Exposure, Genetic Factors, and Cognitive Developmental Delay

Zhenxian Jia,
Hongling Zhang,
Ling Yu
et al.

Abstract: ImportanceAlthough the effects of lead (Pb) exposure on neurocognition in children have been confirmed, the individual associations of prenatal Pb exposure and its interaction with genetic factors on cognitive developmental delay (CDD) in children remain unclear.ObjectiveTo investigate the association of prenatal Pb exposure and its interaction with genetic factors with CDD risk.Design, Setting, and ParticipantsWomen in Wuhan, China, who had an expected delivery date between March 2014 and December 2017, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…From a methodological perspective, it is instructive to note that in this study, 1 lead levels in maternal plasma (as opposed to maternal whole blood) were found to be associated with lower cognition scores among offspring. In so doing, Li et al 1 have provided further support to earlier research suggesting that maternal plasma lead, which is typically less than 1% to 5% of the level of lead in maternal whole blood, is not in complete equilibrium with the lead bound to red cells. Nevertheless, it is the component of lead in blood that is bioavailable to cross the placenta and therefore has the most influence on fetal lead exposure and resulting neurotoxic effects.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…From a methodological perspective, it is instructive to note that in this study, 1 lead levels in maternal plasma (as opposed to maternal whole blood) were found to be associated with lower cognition scores among offspring. In so doing, Li et al 1 have provided further support to earlier research suggesting that maternal plasma lead, which is typically less than 1% to 5% of the level of lead in maternal whole blood, is not in complete equilibrium with the lead bound to red cells. Nevertheless, it is the component of lead in blood that is bioavailable to cross the placenta and therefore has the most influence on fetal lead exposure and resulting neurotoxic effects.…”
mentioning
confidence: 71%
“…metal mining and processing, electronic waste, and the use of lead as a food adulterant, primarily in spices. 6 In addition, as the authors mentioned in their introduction, 1 for pregnant women, the mobilization of bone lead stores during pregnancy remains of concern. Left unmentioned is that skeletal stores of lead persist for decades, and in women who have had chronic lead exposure, research has clearly shown that the heightened bone resorption that occurs during pregnancy is accompanied by the increased release of bone lead stores, resulting in elevated circulating lead levels even if women are fastidious in avoiding lead exposure during pregnancy itself.…”
Section: + Related Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies (Liu et al, 2014;Jia et al, 2023;Shah-Kulkarni et al, 2016) focused on maternal exposure and consequent neurological defects, there has been an increase in the investigation of paternal inherited neurological diseases. This is critical as occupational Pb exposure mostly occurs in men (Balachandar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%